PENGARUH VALUE CONSCIOUSNESS, INTEGRITY, DANPERCEIVED EASE TO GET PRODUCT TERHADAP SIKAP DAN NIAT BELI BARANG PALSU DI KOTA TEGAL - Ghea Dwi Rahmadiane (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2016)
The development of theory that related attitude and purchase intention currently were evolved of value consciousness, integrity, and perceived ease of get product. This study aimed to analyze the effect of value consciousness, integrity, and perceived ease of get product on atittude and purchase intention of counterfeiting fashion in Kota Tegal. This research is a quantitative study using a mall intercept method . Determination of the number of samples in this study were as many as 120 respondents with a sampling method used is using probabilility sampling and sampling techniques are stratified random sampling. The analysis using Structural Equation Modeling analysis (SEM). From the results of SEM analysis known model-based development theory in this study were 5 variables and 17 indicators. Based on the hypothesis test the results were known that there were effect toward value consciousness and perceived ease of get product on attitude and purchase intention of counterfeiting fashion, although there were no effect toward integrity on attitude and purchase intention in Kota Tegal.Keywords : counterfeiting fashion, purchase intention, attitude, value consciousness,integrity, perceived ease of get product